1998
DOI: 10.1063/1.121392
|View full text |Cite
|
Sign up to set email alerts
|

Space-charge-limited charge injection from indium tin oxide into a starburst amine and its implications for organic light-emitting diodes

Abstract: We have investigated the hole-injection characteristics from indium tin–oxide (ITO) into 4,4′,4″-tris{N,-(3-methylphenyl)-N-phenylamino}triphenylamine (m-MTDATA) and have measured the hole-carrier drift mobility of this compound in single-layer ITO/m-MTDATA/Au structures. We have found that ITO is able to provide trap-free space-charge-limited currents over a wide range of film thicknesses and have established unambiguously that the ITO/m-MTDATA is an ideal Ohmic contact at high electric fields. Our observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 13 publications
8
71
0
Order By: Relevance
“…As seen from the results of Fig. 14(a) (Giebeler et al, 1998) at ITO and m-MTDATA interface was reported. Whereas, the NPB hole only device had reported to have the injection limited current behavior.…”
Section: Wwwintechopencomsupporting
confidence: 57%
“…As seen from the results of Fig. 14(a) (Giebeler et al, 1998) at ITO and m-MTDATA interface was reported. Whereas, the NPB hole only device had reported to have the injection limited current behavior.…”
Section: Wwwintechopencomsupporting
confidence: 57%
“…The hole-drift mobilities of of 2-TNATA and p-BPD are also similar to those of m-MTDATA (2.7 X 10"5 cm2V"is"1) and TPD (1.1 X 10"3 cm2V"is"1) [15].…”
Section: Properties Of 2-tnata and P-bpdsupporting
confidence: 50%
“…It was not only attributed to failure of the Ohmic contact presumption at the electrode/organic interface, but also to the energy barriers between the organic layers. On the contrary, the SCLC model is easily accepted in much simpler structures, such as polymer LEDs [32] and single layer hole-only small molecular devices [33].…”
Section: Space Charge Limited Current (Sclc)mentioning
confidence: 99%
“…They are inherently advantageous as lowvoltage [32], miniaturizable [33], and flexible light sources [34,35]. Electrophosphorescent green and blue OLEDs with an external quantum efficiency of ~20% and ~12%, respectively, have been reported [35].…”
Section: Introductionmentioning
confidence: 99%